Perianal Basal Cell Carcinoma - Isil Bulur; Emine Boyuk; Zeynep Nurhan Saracoglu; Deniz Arik (Karger Publishers, 2015)
Basal cell carcinoma (BCC) is the most common non-melanoma skin cancer. Exposure to ultraviolet light is an important risk factor for BCC development and the disorder therefore develops commonly on body areas that are more exposed to sunlight, such as the face and neck. It is uncommon in the closed area of the body and quite rare in the perianal and genital regions. Herein, we report a 34-year-old patient with perianal BCC who had no additional risk factors.